2015
DOI: 10.1016/j.nut.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a single dose of a flavonoid-rich blueberry drink on memory in 8 to 10 y old children

Abstract: Although findings are mixed, the improvements in delayed recall found in this pilot study suggest that, following acute flavonoid-rich blueberry interventions, school-aged children encode memory items more effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 22 publications
6
88
0
Order By: Relevance
“…Blueberries have been shown to have positive cognitive benefits in two acute, cross-over designed studies in school-aged children (ages 7-10). The first study 100 showed that consumption of a flavonoid-rich blueberry (200 g) drink led to significantly better delayed word-list recall, compared to a matched vehicle group, on the Rey auditory-verbal learning test, suggesting more effective coding of memory items. However, there was no benefit of blueberry intervention on measures of attention, response inhibition, or visuospatial memory, and a negative impact on proactive interference.…”
Section: Dietary Interventions With Polyphenolic-rich Foods Can Impromentioning
confidence: 99%
See 1 more Smart Citation
“…Blueberries have been shown to have positive cognitive benefits in two acute, cross-over designed studies in school-aged children (ages 7-10). The first study 100 showed that consumption of a flavonoid-rich blueberry (200 g) drink led to significantly better delayed word-list recall, compared to a matched vehicle group, on the Rey auditory-verbal learning test, suggesting more effective coding of memory items. However, there was no benefit of blueberry intervention on measures of attention, response inhibition, or visuospatial memory, and a negative impact on proactive interference.…”
Section: Dietary Interventions With Polyphenolic-rich Foods Can Impromentioning
confidence: 99%
“…However, there was no benefit of blueberry intervention on measures of attention, response inhibition, or visuospatial memory, and a negative impact on proactive interference. 100 The second study 100 by the same group examined cognition at baseline, and then 1.15, 3, and 6 h after consuming placebo (vehicle) or blueberry drinks containing 15 or 30 g freeze-dried wild blueberry (WBB) powder. Consumption of WBB powder improved recall at 1.15 h, improved delayed word recognition, which was sustained at each time point measured, and improved accuracy on a challenging interference task at 3 h. The best cognitive performance was seen after the 30 g dose, and particularly on those tasks with a higher cognitive demand.…”
Section: Dietary Interventions With Polyphenolic-rich Foods Can Impromentioning
confidence: 99%
“…This is as a result of monoamine levels, particularly for dopamine, being shown to increase during cognitive tasks (which assess working memory and attention) with a positive correlation with task performance [21]. An acute effect on cognition by fruit anthocyanin supplementation has also been observed in children [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main pathways linking blood pressure to cognitive degeneration is the decline in vascular reserve capacity which is associated with impaired neurovascular coupling [16]. Despite evidence from epidemiological and intervention studies indicating that anthocyanin intake is linked with improved cognition [15,17] and a slower cognitive decline [18], the mechanisms by which anthocyanins may exert acute effects on brain function remains unclear and evidence is inconsistent. A crossover study [19] found that high anthocyanin cherry juice consumption did not result in any significant acute effects on a battery of cognitive tests in either younger or older adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation